The Recovery Of Some Of The Soil Chemical Properties And The Growth Of Sengon solomon Plant (Falcataria moluccana (Miq.) Barneby & Grimes) By Composting Desmodium ovalifolium on the Land Of Former Coal Mine - Itang Mahbub; Gindo Tampubolon; Irianto Irianto (Jurnal Silva Tropika, 2020)
The analysis results of the former coal mine c-organik content have range from 0,08-1,58 % which is very low .The low C-organik content is most likely due to activities backfilling that change the horizon structure of the native land . One effort to be made to improve a material organic land is by adding organic fertilizers into holes planting. The research was done in the area concession mining PT Nan Riang Dusun Mudo Village Muara Tembesi Sub-district Batanghari Regency. Soil analysis is done in the laboratory chemical and soil fertility Agriculture Faculty Jambi University . Research implementation time started in June to October 2019. This research used Randomized Block Design based on cutting the slop . The treatment tried is doses compost Desmodium ovalifolium compared with manure chicken. Factors of Desmodium ovalifolium compost doses ( d ) consisting of four level, and manure chicken ie : 2 kg manure chicken per hole (ka), 1 kg of Desmodium ovalifolium compost per hole (d1), 1,5 kg of Desmodium ovalifolium compost per hole (d2), 2 kg of Desmodium ovalifolium compost (d3) per hole and 2,5 kg of Desmodium ovalifolium compost (d4) per hole. Any level of treatment is repeated 5 times so acquired 25 experiments. The results of research claim Desmodium ovalifolium compost possessing good qualities and relatively similar in quality with manure chicken, The distribution of Desmodium ovalifolium compost treatments did not make a significant effect toward the height and diameter of sengon plants and chemical properties of the land . The result of different doses of treatment compost is not significant. Keywords: The Former Coal Mine, Desmodium ovalifolium Compost and Sengon Plant